Otimização geométrica e análise operacional em hidrociclones modulares utilizando fluidos newtonianos - Quintino, Davi Batista (2019)
The separation of solid particles present in high viscous fluid mixtures is required in several industrial operations, such as in petroleum production, food and mineral processing. In the oil and gas industries, in addition to the environmental concern, there is also the need to remove solid particles from the fluid phase to eliminate interferences in the operation of equipment and controls. Suspension viscosity is an operational variable not widely addressed in the hydrocyclone separation process, and studies involving solids in Newtonian fluids are commonly limited to solid-water suspensions. In order to contribute to the knowledge of the rheology of the fluid applied to the separation process in hydrocyclones, the present work had the aim of separating particles of sucrose solutions with different viscosities by hydrocyclone. For this, the best configuration was firstly evaluated, which concomitantly produced a high rate of collection of solids and reduced loss of liquid by underflow. In this first part, two geometric variables, underflow diameter and angulation of the conical section, were analyzed in five levels, totalizing 25 trials. Through multiple regression of the responses obtained for separation efficiency and split ratio, empirical mathematical models and response surfaces were generated. After selecting the best separation configuration, this geometry was used in a Central Composite Design, consisting of 17 trials, which aimed to analyze the influence of three variables: viscosity, pressure and solids concentration. The viscosity levels studied ranged from 9.88 to 26.12 cP, the pressure values from 19.18 to 40.82 psi, and the suspension solid concentration levels from 1.65 to 4.35% in volume. With the accomplishment of the Central Composite Design, it was obtained high values of global separation efficiency (73.1 to 93.3%), still maintaining low split ratios (average value of 19.8%). The operating capacity, reduced efficiency, Euler number and cutting diameter were also evaluated. Through statistical analysis and model equations, the maximization of the separation was associated with high pressures and lower values of viscosity, the latter being the most significant variable in the analyzed responses. Lastly, CFD techniques were applied in order to simulate the internal flow of the "optimal" hydrocyclone. In the simulations, the tangential and axial velocity profiles were analyzed in four positions of the separator, in which a high influence of the viscosity could be observed in the tangential velocity profile.